2020
DOI: 10.3390/en13184625
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Thermal Retrofitting on Annual Energy Demand for Heating in Multi-Family Buildings

Abstract: The paper presented the analysis of heat consumption for heating in multi-family residential buildings before and after thermal retrofitting. The analysis involved four groups of buildings, i.e., 43 buildings in total, located in various localities, belonging to one weather station. The predicted level of energy savings resulting from thermal retrofitting was achieved from the energy audits. The actual heat consumption, following the calculation into so-called external standard conditions, was obtained based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
(44 reference statements)
0
6
0
Order By: Relevance
“…They have also recognized that the same may be true for new buildings because of the poor output of radiators when working at very low temperatures. They explained the reason but could not provide sustainable solutions, except noting that radiators were already oversized in many cases in existing buildings.Życzyńska, A. et al have investigated the impact of thermal retrofitting in Polish buildings on their annual energy budget [34]. They concluded that the thermal retrofitting in multi-family apartments that they have investigated reduced their heating demand up to 43%.…”
Section: Low-temperature District Energy Systemsmentioning
confidence: 99%
“…They have also recognized that the same may be true for new buildings because of the poor output of radiators when working at very low temperatures. They explained the reason but could not provide sustainable solutions, except noting that radiators were already oversized in many cases in existing buildings.Życzyńska, A. et al have investigated the impact of thermal retrofitting in Polish buildings on their annual energy budget [34]. They concluded that the thermal retrofitting in multi-family apartments that they have investigated reduced their heating demand up to 43%.…”
Section: Low-temperature District Energy Systemsmentioning
confidence: 99%
“…The analysis of the methodology to prepare the building energy certificates and related standards indicate that many parameters affect the value of the building indicator for nonrenewable annual primary energy consumption for heating (PE H ). The value of the PE H index depends on the value of the building indicators of usable, final energy and primary energy factor [3,[19][20][21]. The building usable energy demand, expressed through the usable energy demand, is influenced by: climatic conditions related to the location of the building, its orientation relative to world directions, internal heat gains and building envelope parameters, such as thermal insulation of building partitions, protection properties against wind, building glazing, shading of transparent partitions and their ability to transmit solar radiation [18,[22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…This applies to buildings regardless of their location, i.e., in urban and rural areas. First of all, local government units indicated educational facilities for thermal retrofitting investments, and then others, such as offices, related to medical services or cultural activities of the city or commune [7,8]. Co-financing programs were particularly useful in units that did not have a sufficient budget to carry out a thermal retrofitting investment from their own funds [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The second one, which takes into account the total efficiency of the heating system, is called the final energy consumption for heating (FE H ). The third is called the non-renewable primary energy index for heating (PE H ), the value of which additionally depends on the type of fuel or energy used to cover the heating needs of the building [8,17].…”
Section: Introductionmentioning
confidence: 99%